2008
DOI: 10.1007/s10811-008-9383-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of temperature and light intensity on growth and extracellular polymeric substance production by the cyanobacterium Arthrospira platensis

Abstract: The effects of light intensity and temperature on Arthrospira platensis growth and production of extracellular polymeric substances (EPS) in batch culture were evaluated using a three-level, full-factorial design and response surface methodology. Three levels were tested for each parameter (temperature: 30, 35, 40°C; light intensity: 50, 115, 180 μmol photons m −2 s −1 ). Both growth and EPS production are influenced mainly by the temperature factor but the interaction term temperature*light intensity also had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 21 publications
8
60
1
Order By: Relevance
“…Several works are available that report the effects of light intensity both in diazotrophic and non-diazotrophic conditions. In general, the EPS production showed a positive linear effect with light intensity especially in the presence of combined nitrogen for different Nostoc species [5], Arthrospira platensis [6] and Cyanothece sp. CCY 0110 [7].…”
Section: Introductionmentioning
confidence: 95%
“…Several works are available that report the effects of light intensity both in diazotrophic and non-diazotrophic conditions. In general, the EPS production showed a positive linear effect with light intensity especially in the presence of combined nitrogen for different Nostoc species [5], Arthrospira platensis [6] and Cyanothece sp. CCY 0110 [7].…”
Section: Introductionmentioning
confidence: 95%
“…The influence of temperature on growth and biochemical composition depends on the irradiance level and vice versa [63,[67][68][69]. For most algae, the combinations of high temperatures with high light intensities or low temperatures with high irradiance levels are unfavorable conditions at which negligible growth is observed.…”
Section: Effect Of Cultivation Temperature Irradiance and Their Intementioning
confidence: 99%
“…In Scytonema, increasing irradiance levels gradually increases antibiotic production [87]. The increase of light intensity stimulates the secretion of polymeric substances from Arthrospira platensis [68] and improves its carotenoid content [88].…”
Section: Effects Of Temperature Irradiance and Their Interaction On mentioning
confidence: 99%
“…Several recent studies on the influence of light intensity (Friedman et al, 1991;Moreno et al, 1998;Otero and Vincenzini, 2003;Trabelsi et al, 2009;Yu et al, 2010;Mota et al, 2013) and wavelengths (Ehling-Schulz et al, 1997;Chen et al, 2009) on EPS yield have been reported. Different light regimens (continuous light and light-dark cycles) do not significantly affect the monosaccharidic composition of EPS (Vincenzini et al, 1993;De Philippis and Vincenzini, 1998).…”
mentioning
confidence: 99%
“…1). (Friedman et al, 1991;Moreno et al, 1998;Otero and Vincenzini, 2003;Trabelsi et al, 2009;Yu et al, 2010;Mota et al, 2013), suggesting that energy availability significantly affects the EPS biosynthesis of cyanobacteria. Higher light intensity results in higher EPS production, which may constitute mechanism of releasing the excess energy absorbed by the cells (Mota et al, 2013) and increasing CO2 fixation rate in the cells under high light intensity.…”
mentioning
confidence: 99%